2007
DOI: 10.1167/7.2.20
|View full text |Cite
|
Sign up to set email alerts
|

Crowding and eccentricity determine reading rate

Abstract: Bouma's law of crowding predicts an uncrowded central window through which we can read and a crowded periphery through which we cannot. The old discovery that readers make several fixations per second, rather than a continuous sweep across the text, suggests that reading is limited by the number of letters that can be acquired in one fixation, without moving one's eyes. That "visual span" has been measured in various ways, but remains unexplained. Here we show (1) that the visual span is simply the number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
357
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(389 citation statements)
references
References 83 publications
30
357
1
1
Order By: Relevance
“…Studies of crowding (Bouma, 1970;Pelli et al, 2007;Toet & Levi, 1992) have indicated that the letters in our experiments-presented at a retinal eccentricity of 6.0°-should be free from crowding when separated by about 3.0° or more. In fact, they were separated by 8.5° (see Figure 1a), suggesting that crowding played no appreciable role in either condition.…”
Section: A Bilateral Advantage?mentioning
confidence: 59%
“…Studies of crowding (Bouma, 1970;Pelli et al, 2007;Toet & Levi, 1992) have indicated that the letters in our experiments-presented at a retinal eccentricity of 6.0°-should be free from crowding when separated by about 3.0° or more. In fact, they were separated by 8.5° (see Figure 1a), suggesting that crowding played no appreciable role in either condition.…”
Section: A Bilateral Advantage?mentioning
confidence: 59%
“…Assuming college-students read anywhere from 2-8 hours/day, at a rate of about 300 words/minute (Pelli, Tillman, Freeman, Su, Berger, & Majaj, 2007;Taylor, 1965), this would translate into many more words read than spoken/day 4 (300*60*2= 36,000 and 300*60*8=144,000).…”
Section: Frequency-lag For Production Versus Comprehensionmentioning
confidence: 99%
“…20 and 21). Recognition is impaired when letters are closer than a critical spacing (19), which is proportional to eccentricity but independent of print size (22).…”
mentioning
confidence: 99%
“…Crowding mostly affects peripheral vision in normal adult readers (22), but it also affects central vision in school-aged children (23). Moreover, there is mounting evidence that children with developmental dyslexia are more influenced by crowding than agematched controls, even under optimal viewing condition (14-17, 24, 25).…”
mentioning
confidence: 99%
See 1 more Smart Citation